Decision-making behavior of rural residents' domestic waste classification in Northwestern of China ——analysis based on environmental responsibility and pollution perception. (1st December 2021) - Jia, Yajuan; Cheng, Shujun; Shi, Rui
Abstract: In the background of growing rural domestic waste pollution, encouraging the source classification of rural domestic waste is a critical way to address the inadequacies of rural environmental problems. Using the micro-survey data of rural residents in Shaanxi province, China, this paper explores the decision-making behavior (classification willingness and degree of classification) of rural residents' domestic waste through a double-hurdle model (DHM). The results show that among the 1374 rural residents, 1274 samples are willing to be sorted and put into place. Of these, 45.21% of the rural residents are eager to classify household waste into four categories, namely recycling or saleable, food waste or perishable, toxic and harmful, and others. Besides, household income has a significantly negative impact on the domestic waste classification willingness of rural residents while the number of education years positively impacts the degree of rural domestic waste classification. It is an indication that the sense of environmental responsibility significantly and positively influences the decision-making behaviors of rural residents, not only promoting their willingness to classification but also increasing their degree of classification; the psychological perception of rural residents about the pollution of domestic waste significantly increases their willingness and degree of classification. Policy implications are further discussed.